An assessment of private television broadcasting operations in Nigeria - Akpor Ewomazino (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
This study examines the challenges of private broadcasting in Nigeria with particular reference to African Independent Television (AIT), Yenagoa, as the case study. The wake of private broadcasting in Nigeria came with decree 38 of 1992 under the General Ibrahim Babangida Administration. This overtime leads to the dissolution of the monopoly of the publicly-owned media organizations in Nigeria, which held a monopoly and were on a steady increase in terms of their numbers as each state was created and the governor open a medium for their country. However, this study focused on the challenges the private broadcast media faced in operations and how they strive to keep afloat. The functionalist theory, pluralist, and Marxist theories created a fundamental basis for the research work. Using the survey method and questionnaire instrument, the researcher gathered responses from 60 respondents at AIT, Yenagoa, who occupied different organization positions. Thus, the researcher analyzed the data and came up with the findings that even to date, funding, access to equipment, power supply, government regulations, and the need to fully attain digitalization were some of the challenges confronting the African Independent Television (AIT), Yenagoa and by implication the private broadcast media. Therefore, the government, its agencies, CBN, and other stakeholders have been advised to help create a soft landing for private media. They have contributed a lot to improving programs' quality, faster access to new, objective, balanced reporting, and the likes.